2018
DOI: 10.1049/hve.2018.5004
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated ultraviolet weathering investigation on micro‐/nano‐SiO 2 filled silicone rubber composites

Abstract: This study attempts to elucidate whether the addition of micro and/or nano-silica (SiO 2) particles can enhance the resistance of pure polydimethylsiloxane against synergistic effects of UV, temperature and high-voltage stress. Four types of composites (U-SR, M-SR, MN-SR and N-SR) are fabricated by adding micro and/or nano-silica particles and then subjected to multi-stress degradation in a test chamber. Results show that there is an apparent surface discoloration in the form of yellowish pale tint and a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In this method, the water drop was made to fall on the silicone rubber sample surface. The contact angle between the drop and the surface was measured.The contact angle greater than 90 • indicated good hydrophobicity and, less than 90 • indicated that the sample had become hydrophilic [22][23][24][25][26].…”
Section: Effect Of Ageing On the Percentage Weight Change The Contact Angle And Hydrophobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, the water drop was made to fall on the silicone rubber sample surface. The contact angle between the drop and the surface was measured.The contact angle greater than 90 • indicated good hydrophobicity and, less than 90 • indicated that the sample had become hydrophilic [22][23][24][25][26].…”
Section: Effect Of Ageing On the Percentage Weight Change The Contact Angle And Hydrophobicitymentioning
confidence: 99%
“…Nazir et al investigated to understand the addition of nano/micro SiO 2 particles in enhancing the UV weathering resistance of RTV silicone rubber. Nazir et al also studied the effect of different micro-fillers, like ATH, aluminum nitride (AlN) and boron nitride (BN) in improving the tracking and erosion properties of silicone rubber [22,23]. Guo, Y. et al fabricated silicone rubber with platinum/amino-silane, which enhances the tracking resistance during dry band arcing period [24].…”
Section: Introductionmentioning
confidence: 99%
“…Yuan and co-workers studied the dielectric loss of SiR/SiO 2 composites under AC corona at different AC voltages and observed that change in dielectric loss remained under 1% after 24 days of corona aging at 3 kV [27]. Degradation of silica filled silicone rubber under accelerated ultraviolet weathering conditions has also been reported [28]. The dielectric properties of newly manufactured and 500 kV composite insulators operated shed and housing material was determined under hydrothermal conditions (20 • C, 90% humidity).…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, polymer composites offer multiple improvements over simple polymers [ 1 ]. Polymer composites have an edge over conventional polymers due to their improved stability, greater lifespan, and enhanced physical, electrical, optical, and mechanical properties [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The development of charge-storing devices for higher storage capability needs to meet challenging criteria such as higher dielectric permittivity, low dielectric loss, and better mechanical strength [ 9 ].…”
Section: Introductionmentioning
confidence: 99%